Analysis of the Side Effects of Long-Term Proton Pump Inhibitor (PPI) Use in Patients with Gastroesophageal Reflux Disease (GERD) - Nurhafidah, Zahra; Hilmi, Indah Laily; Sudarjat, Hadi (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Proton Pump Inhibitors (PPIs) are widely prescribed to manage gastrointestinal disorders, especially gastroesophageal reflux disease (GERD). However, long-term PPI use has been linked to serious side effects and potential complications. Objective: This study aims to analyze the side effects associated with prolonged PPI use in patients with GERD. Methods: A systematic review was conducted using Google Scholar and PubMed databases with relevant keywords. Article selection was carried out carefully based on inclusion and exclusion criteria to ensure the quality and relevance of the data. Additionally, a bibliometric analysis was performed to explore research trends related to the long-term use of PPIs. Results: The review found that prolonged PPI use is associated with various adverse effects, including an increased risk of dementia, progression of chronic kidney disease (CKD), gastric cancer, bone fractures, Frailty Syndrome, hypomagnesemia, iron deficiency, vitamin B12 deficiency, myocardial infarction, and esophageal cancer. The bibliometric analysis also indicated a growing trend of research focusing on the safety and complications of long-term PPI use. Conclusion: Long-term PPI therapy carries significant risks. Therefore, regular monitoring and appropriate discontinuation strategies are essential when using PPIs over extended periods to minimize potential harm.